2007
DOI: 10.1097/jsa.0b013e3181595bd2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using Allograft

Abstract: The author presents his current technique for reconstructing an isolated anterior cruciate ligament rupture using an allograft. The specific positioning and surgical steps are presented. Dangers to be avoided are included, which have led to this current technique. The step-by-step technique should enable the surgeon to reconstruct the ligament with little difficulty. The postoperative course including rehabilitation is discussed from postoperative day 1 to full restoration of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Subsequent research, however, has shown that periarticular control and direct ACL reattachment do not work to repair ACL injuries. [3][4][5][6][7] Today, the treatment of choice is to use autograft or allograft tissue to replace the torn ligament.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent research, however, has shown that periarticular control and direct ACL reattachment do not work to repair ACL injuries. [3][4][5][6][7] Today, the treatment of choice is to use autograft or allograft tissue to replace the torn ligament.…”
mentioning
confidence: 99%
“…Allografts have the advantage of being available in adequate size and length, which presents a low risk of disease transmission and allows the patient's extensor and flexor mechanisms to remain intact. 3 Graft choice is based on surgeon and patient preference, as well as the patient's age and activity level. Results of studies indicate that autografts and allografts used in ACL reconstruction have similar biomechanical properties and compare favorably with the intact ACL.…”
mentioning
confidence: 99%
“…The transtibial method and the anteromedial portal method are both considered single incision techniques [121,148]. In the transtibial method ( Figure 5.8), the tibial tunnel is created through an anteromedial incision and the femoral tunnel is created through the tibial tunnel with the leg correctly positioned [149]. In 2009, 70% of orthopaedic surgeons reported using the transtibial technique [143].…”
Section: Single Bundle Reconstructionmentioning
confidence: 99%